2019
DOI: 10.1177/2192568219873885
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Cement Discoplasty for the Treatment of Advanced Degenerative Disc Conditions: A Case Series Analysis

Abstract: Study Design: Retrospective analysis. Level of evidence III. Objectives: To describe the results after a minimum 1-year follow-up in patients treated with percutaneous discoplasty (PD), a minimally invasive technique to treat low back pain in elderly patients with advanced degenerative disc disease. The procedure consists in improving stability by injecting bone cement in a severely degenerated pneumodisc. There are few reports in the literature about this technique. Methods: Fifty-four patients with advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Percutaneous cement discoplasty (PCD) is a MIS procedure, where the vacuum space in the intervertebral disc is filled out with percutaneously injected PMMA (Polymethylmethacrylate), which provides a segmental stabilizing effect and indirect decompression of the neuronal elements due to the increase of the spinal canal dimensions. The technical details, the clinical effect and safety issues of the procedure have been previously published and the usage of the technique has also been supported by a prospective radiological study [ [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous cement discoplasty (PCD) is a MIS procedure, where the vacuum space in the intervertebral disc is filled out with percutaneously injected PMMA (Polymethylmethacrylate), which provides a segmental stabilizing effect and indirect decompression of the neuronal elements due to the increase of the spinal canal dimensions. The technical details, the clinical effect and safety issues of the procedure have been previously published and the usage of the technique has also been supported by a prospective radiological study [ [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, partial VP could be an indication for percutaneous discoplasty, with some concerns regarding the increased risk of adjacent fractures in the absence of subchondral sclerosis (type 2A), the same concept should be applied to type 3A, as we believe that subchondral sclerosis plays a role in preventing vertebral fracture. However, in our case series of 54 patients treated with PD, 11 only 1 case suffered vertebral fracture after PD in a type 2A vacuum and required vertebroplasty, having just a few evidence in the literature, this concept is just theoretical and needs to be supported by biomechanical and clinical studies.…”
Section: Discussionmentioning
confidence: 85%
“…This treatment is based on the concept of polymethyl methacrylate (PMMA) injection in the disc space in advances stages of degeneration with vacuum phenomenon, acting as a stabilizer intervertebral spacer, this treatment has demonstrated low back and leg pain improvement and partial correction of spinal balance in unbalanced cases with low complication rates and short hospital stay. [9][10][11] Yamada et al 23 reported improvement in low back pain in 109 patients with degenerative lumbar scoliosis treated with percutaneous intervertebral-vacuum polymethylmethacrylate injection (PIPI), although the name of the procedure differs, the concept is the same. A proper patient selection is necessary, with correct identification of the pain source and some image characteristics may contribute to decrease the risk of some complications such as adjacent vertebral fracture, cement leakage, or disc material protrusion associated with PMMA injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations